Species Diversity, Biomass Production and Carbon Sequestration Potential in the Protected Area of Uttarakhand, India - Geetanjali Upadhyay; Lalit M. Tewari; Ashish Tewari; Naveen Chandra Pandey; Sheetal Koranga; Zishan Ahmad Wani; Geeta Tewari; Ravi K. Chaturvedi (Plants)
Ecosystem functioning and management are primarily concerned with addressing climate change and biodiversity loss, which are closely linked to carbon stock and species diversity. This research aimed to quantify forest understory (shrub and herb) diversity, tree biomass and carbon sequestration in the Binsar Wildlife Sanctuary. Using random sampling methods, data were gathered from six distinct forest communities. The study identified 271 vascular plants from 208 genera and 74 families. A notable positive correlation (r2 = 0.085, p < 0.05) was observed between total tree density and total tree basal area (TBA), shrub density (r2 = 0.09), tree diversity (D) (r2 = 0.58), shrub diversity (r2 = 0.81), and tree species richness (SR) (r2 = 0.96). Conversely, a negative correlation was found with the concentration of tree dominance (CD) (r2 = 0.43). The Quercus leucotrichophora, Rhododendron arboreum and Quercus floribunda (QL-RA-QF) community(higher altitudinal zone) exhibited the highest tree biomass (568.8 Mg ha−1), while the (Pinus roxburghii and Quercus leucotrichophora) PR-QL (N) community (lower altitudinal zone) in the north aspect showed the lowest (265.7 Mg ha−1). Carbon sequestration was highest in the Quercus leucotrichophora, Quercus floribunda and Rhododendron arboreum (QL-QF-RA) (higher altitudinal zone) community (7.48 Mg ha−1 yr−1) and lowest in the PR-QL (S) (middle altitudinal zone) community in the south aspect (5.5 Mg ha−1 yr−1). The relationships between carbon stock and various functional parameters such as tree density, total basal area of tree and diversity of tree showed significant positive correlations. The findings of the study revealed significant variations in the structural attributes of trees, shrubs and herbs across different forest stands along altitudinal gradients. This current study’s results highlighted the significance of wildlife sanctuaries, which not only aid in wildlife preservation but also provide compelling evidence supporting forest management practices that promote the planting of multiple vegetation layers in landscape restoration as a means to enhance biodiversity and increase resilience to climate change. Further, comprehending the carbon storage mechanisms of these forests will be critical for developing environmental management strategies aimed at alleviating the impacts of climate change in the years to come.